How room rates drive occupancy: A case study from The Laguna, a Luxury Collection Resort & Spa, Nusa Dua - I Gede Tito Yuda Pradana Jaya; Putu Diah Sastri Pitanatri; Ni Made Suastini (School of Tourism, Universitas Ciputra Surabaya, 2023)
The occupancy rate is a critical indicator of success for hotels, serving as a gauge of the proportion of rooms sold relative to the total available inventory, and is typically assessed on a daily, monthly, and annual basis. For hotels striving to optimize both room occupancy and revenue, the execution of a strategically designed marketing mix is paramount, with pricing as a central component. Establishing an optimal price point is a significant challenge for hotel management; the price must be calibrated to avoid perceptions of being excessively low or high by consumers, while simultaneously ensuring profitability and competitive positioning. Recognizing this, errors in pricing strategy can have a profound impact on a hotel’s occupancy rate. This study aims to investigate the relationship between room rates and occupancy at The Laguna, a Luxury Collection Resort & Spa. The research employs secondary data encompassing room prices and occupancy rates and utilizes a comprehensive suite of analytical techniques—including classic assumption tests, simple linear regression, correlation coefficient analysis, determination coefficient analysis, and t-tests—facilitated by SPSS version 25 software. The findings reveal a statistically significant relationship between room pricing and occupancy rates. Notably, the determination analysis suggests that room rates exert a substantial 64.60% influence on room occupancy, while the remaining 35.40% is attributed to other factors not examined in this study, such as product and service quality, and promotional strategies.